Physiological effects of stress related to helicopter travel in Federal Emergency Management Agency search-and-rescue canines. (7th June 2017) - Perry, E.; Gulson, N.; Liu Cross, T.-W.; Swanson, K. S.
Abstract: Working canines are deployed by the Federal Emergency Management Agency (FEMA), as part of a National Disaster Response Plan. Stress associated with helicopter flight and the resulting physical effects on the dog are unknown. Our objective was to test the hypotheses that (1) helicopter travel affects the physiology and faecal microbiota of working canines, but that (2) physiological consequences of helicopter travel will not negatively affect their work performance. A total of nine FEMA canines were loaded onto helicopters and flown for 30 min in July 2015. Rectal temperature, behavioural stress indicators and saliva swabs (for cortisol) were collected at baseline, loading, mid-flight and post-flight. After flight, canines completed a standardised search exercise to monitor work performance. Faecal samples were collected for microbial DNA extraction and Illumina sequencing. All canines were on a standardised diet (CANIDAE ® Grain Free PURE Land ® ) for 3 weeks prior to the study. Visible indicators of stress were observed at loading and at mid-flight and corresponded with an increase ( P < 0·05) in salivary cortisol from 5·4 µg/l (baseline) to 6·4 µg/l (loading). Additionally, rectal temperature increased ( P < 0·05) from 38·61°C (baseline) to 39·33°C (mid-flight) and 39·72°C (post-flight). Helicopter travel did not affect search performance ( P > 0·05). We found that α- and β-diversity measures of faecal microbiota were not affected ( P > 0·05). Our data suggest that although helicopter travel may cause physiological changes that have been associated with stress in working dogs, it does not make an impact on their search performance or the stability of faecal microbiota.